A Stochastic Approach to Energy Cost Minimization in Smart-Grid-Enabled Data Center Network - Ghassemi, Abolfazl; Goudarzi, Pejman; Mirsarraf, Mohammad R.; Gulliver, T. Aaron (Journal of Computer Networks and Communications, 2019)
We propose a Lyapunov drift-plus-penalty- (LDPP-) based algorithm to optimize the average power cost for a data center network. In particular, we develop an algorithm to minimize the operational cost using real-time electricity pricing with the integration of green energy resources from the smart grid. The LDPP technique can achieve significant energy cost savings under quality of service (QoS) constraints. Numerical results are presented to evaluate and validate our solution. These results illustrate significant operational/energy cost reductions for a data center network over the conventional approach which optimizes the predicted values of stochastic parameters under a fixed QoS constraint.